A key role for parabrachial nucleus CGRP neurons in FGF1-Induced anorexia - Jarrad M. Scarlett; Eunsang Hwang; Nicole E. Richardson; Caeley L. Bryan; Ingrid Redford; Emily Quah; Erik Tyr R. Odderson; Pique P. Choi; Matthew K. Hwang; Bao Anh Phan; Kelly Kadlec; Kimberly M. Alonge; et al. (Molecular Metabolism)
In addition to sustained glucose lowering, centrally administered fibroblast growth factor 1 (FGF1) induces a potent but transient anorexia in animal models of type 2 diabetes. To investigate the mechanism(s) underlying this anorexic response, the current work focused on a specific neuronal subset located in the external lateral subdivision of the parabrachial nucleus marked by the expression of calcitonin gene-related peptide (elPBNCGRP neurons). These neurons can be activated by withdrawal of upstream GABAergic inhibitory input and are implicated as mediators of the adaptive response (including anorexia) to a wide range of aversive stimuli. To determine if FGF1-induced anorexia is associated with elPBNCGRP neuron activation, we employed adult male CalcaCre:GFP/+ transgenic mice in which GFP is fused to Cre recombinase driven by the CGRP-encoding gene Calca. Here, we show that FGF1 activates elPBNCGRP neurons, both after intracerebroventricular (icv) injection in vivo and when applied ex vivo in a slice preparation, and that the mechanism underlying this effect depends upon reduced GABAergic input from neurons lying upstream. Consistent with this interpretation, we report that the anorexic response to icv FGF1 is reduced by ∼70% when elPBNCGRP neurons are silenced using chemogenetics. Last, we report that effects of icv FGF1 injection on both elPBNCGRP neuron activity and food intake are strongly attenuated by systemic administration of the GABAA receptor agonist Bretazenil. We conclude that in adult male mice, elPBNCGRP neuron activation is a key mediator of FGF1-induced anorexia, and that this activation response is mediated at least in part by withdrawal of GABAergic inhibition.